Jawabanmu

2014-06-26T15:37:55+07:00
3)  f(x) = 1/(x+1) dan g(x) = 2/(3-x)
     (fog)(x) =       1       
                         2    +  3-x 
                      3 - x    3 - x
                  =       1        = - x + 3    Jadi, (fog)^-1(x) = -5x + 3
                         5 - x        -x + 5                                   -x + 1
                         3 - x
4) (g^-1of^-1)(x) = (gof)^-1(x) = 2x-5  ⇔ (gof)(x) = x + 5
                                                  3x-1                      3x-2
     g(f(x)) = x + 5
                   3x-2
     g(f(x-2)) = (x-2)+7
                     3(x-2)+4
     g(x) =  x + 7
               3x + 4